2018
DOI: 10.3390/su10072538
|View full text |Cite
|
Sign up to set email alerts
|

How to Avoid Pigeonholing the Environmental Manager?

Abstract: Abstract:The research investigates the role the environmental manager plays to ensure a successful (or not) implementation of environmental performance within an organization. It is based on interviews of 5-7 actors per company within a sample of 7 companies (42 interviews). We build upon bias of perception of the various actors interviewed within each company to define 4 paradoxes related to the roles and mission of the environmental manager that hinder proper efficiency of environmental management at company… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…The presence of the architect's perspective was further found in relation to challenges experienced by companies working with sustainability, about the difficulty to set a direction, doubts of where to set priorities and what KPIs to measure; calling for an architect's perspective to establish rational priorities, indicators and goals [12,28,62]. The importance of having capabilities specified in the company's organigram was highlighted at Company D which echoes with the findings of Boucher et al [39]. On the other hand, we found that the discussion around having environmental targets for products varied depending on the context of the company, and more particularly on the nature of its products and drivers to develop environment-friendly products.…”
Section: Presence Of the Four Lenses Of Organizationsmentioning
confidence: 77%
See 3 more Smart Citations
“…The presence of the architect's perspective was further found in relation to challenges experienced by companies working with sustainability, about the difficulty to set a direction, doubts of where to set priorities and what KPIs to measure; calling for an architect's perspective to establish rational priorities, indicators and goals [12,28,62]. The importance of having capabilities specified in the company's organigram was highlighted at Company D which echoes with the findings of Boucher et al [39]. On the other hand, we found that the discussion around having environmental targets for products varied depending on the context of the company, and more particularly on the nature of its products and drivers to develop environment-friendly products.…”
Section: Presence Of the Four Lenses Of Organizationsmentioning
confidence: 77%
“…Through the structural lens, scholars have reported the lack of strategy or concrete goals to integrate environmental aspects in products [17,[61][62][63], the absence of a predefined toolset to support ecodesign decision-making, and the lack of formal presence of ecodesign aspects in project assessment frameworks [19,22], and performance measurement systems [61,63]. Additionally, scholars reported lack of clear responsibility allocation and presence in the organigram [17,39], and the absence of specific mechanisms to collect information related to sustainability from the market and regulation [62]. Scholars have recommended exploring possibilities to integrate ecodesign aspects in existing processes [11,12,19,21,[64][65][66], in order to create an official arena for discussing environmental aspects [65], and investigating how to formally integrate ecodesign aspects in the different levels of organization, i.e., operational, tactical and strategic [18].…”
Section: The Four-lens View Of Organizations In the Context Of Ecodesmentioning
confidence: 99%
See 2 more Smart Citations